Analysis of the relationship between neutron dose and Cerenkov photons under neutron irradiation through Monte Carlo method. (October 2016) - Shu, Diyun; Tang, Xiaobin; Guan, Fada; Geng, Changran; Yu, Haiyan; Gong, Chunhui; Zhang, Xiaodong; Chen, Da
Abstract: To theoretically explore the feasibility of neutron dose characterized by Cerenkov photons, the relationship between Cerenkov photons and neutron dose in a water phantom was quantified using the Monte Carlo toolkit Geant4. Results showed that the ratio of the neutron dose deposited by secondary electrons above Cerenkov threshold energy to the total neutron dose is approximately a constant for monoenergetic neutrons from 0.01 eV to 100 eV. With the initial neutron beam energy from 0.01 eV to 100 eV, the number of Cerenkov photons has a good correlation with the total neutron dose along the central axis of the water phantom. The changes of neutron energy spectrum and mechanism analysis also explored at different depths. And the ratio of total neutron dose to the intensity of Cerenkov photons is independent of neutron energy for neutrons from 0.01 eV to 100 eV. These findings indicate that Cerenkov radiation also has potential in the application of neutron dose measurement in some specific fields. Highlights: Relationship between Cerenkov photons and neutron dose in water was investigated. Neutron dose has good correlation with Cerenkov photons between 0.01 eV and 100 eV. Ratio of neutron dose to Cerenkov photons is energy-independent at specified case. Cerenkov radiation also has the potential application in neutron dose measurement.